Pengembangan Bahan Ajar Menulis Narasi Berbasis Model Pembelajaran Brainwriting untuk Meningkatkan Keterampilan Menulis Narasi Siswa Kelas V Sekolah Dasar - Romansyah, Desta; Muktadir, Abdul; Widi Winarni, Endang (Jurnal Kajian Pendidikan Dasar, 2025)
This study aims to develop teaching materials for writing narratives based on the brainwriting learning model to improve the narrative writing skills of fifth grade students of SD Muhammadiyah 65 Sumber Harta. The type and method of research used in this study is research and development (R&D). This research was conducted at SD Muhammadiyah 65 Sumber Harta. Data collection techniques used needs questionnaires, response questionnaires and tests. The research instruments used needs analysis instruments, expert validation instruments, product trial instruments, and product effectiveness test instruments. Data analysis in this study was carried out by analyzing expert validity data, rater/rater agreement, user responses, readability tests, and pretest and post-test n-gain data analysis techniques. Based on the results of the study, it can be concluded that the teaching materials for writing narratives based on the brainwriting model to improve narrative writing skills developed according to material expert validators, language expert validators, and design expert validators are declared suitable for use. Based on the results of the narrative writing skills of fifth grade students of SD Muhammadiyah 65 Sumber Harta, it was found that classically the students' narrative writing skills were above the KKM.